The Gut Microbiome in Health and Disease (Springer International Publishing, 2018)
The book provides an overview on how the gut microbiome contributes to human health. The readers will get profound knowledge on the connection between intestinal microbiota and immune defense systems. The tools of choice to study the ecology of these highly-specialized microorganism communities such as high-throughput sequencing and metagenomic mining will be presented. In addition the most common diseases associated to the composition of the gut flora are discussed in detail. The book will address researchers, clinicians and advanced students working in biomedicine, microbiology and immunology.